Muslim Conversion Narratives in Digital Media: A Critical Discourse Analysis of Belal Chin’s YouTube Testimony - Tri Rina Budiwati; Mutiara Husna; Wiwiek Afifah (Pusat Pelatihan, Riset, dan Pembelajaran Bahasa, 2026)
This research examines the narrative of Muslim conversion through critical discourse analysis. The objective of this study is to analyze a YouTube video entitled “I don't care if I die! I have to become Muslim!”- British Rapper inspiring convert Story!” by using critical discourse analysis of Teun A. van Dijk’s model. The study focuses on the textual analysis, social cognition, and social context of the video. This research is categorized as descriptive qualitative research. The data of this research are the words and sentences of Ashley Belal Chin. The classified data is then analyzed using Van Dijk's three-dimensional concept. The results of this study indicate that the story in the video has three structural dimensions, namely textual analysis, social cognition, and social context. The results of the text include microstructure that focuses on semantic elements (background, detail, meaning, presupposition, and nominalization), superstructure that is coherent from the beginning to the end of the video because each segment is a procession of converts that are interconnected, and macrostructure, which concludes that the theme of the video is the spirit of becoming a Muslim. Furthermore, social cognition shows the existence of schemes and memories that describe the speaker's background when delivering discourse to the audience. Social context refers to the way discourse evolves within society, considering social structures from the perspectives of power and access. Overall, the study provides insights into how digital media articulates and circulates narratives of Muslim conversion.